2021
DOI: 10.1038/s41598-021-00993-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and isotherm modeling of effective adsorption of malachite green as endocrine disruptive dye using Acid Functionalized Maize Cob (AFMC)

Abstract: Cationic Malachite green has been identified as a candidate for the endocrine disruptive compound found in the environment. In this study, the mechanism and isotherm modeling of effective adsorption of cationic malachite green dye onto acid-functionalized maize cob (AFMC) was investigated by batch technique. The operational parameters such as initial concentration (100–600 mg/L); contact time (10–120 min) and pH (3–10) influenced the removal efficiency and quantity adsorbed. A maximum of 99.3% removal efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Our conclusions are comparable with those of other studies conducted for the removal of dyes by adsorption on different materials. Similar findings were published by Ali et al [ 88 ], who explored the adsorption of indigo carmin and Congo Red dyes on calcinated layered double hydroxides, and by Ojediran et al [ 89 ], who inspected the retention of malachite green on acid functionalized maize cob and pointed out that the adsorption does not obey the Langmuir model. Abramian and El-Rassy focused on the adsorption of Orange II dye on a porous titania aerogel [ 79 ] and revealed that the Freundlich isotherm is suitable for describing the process.…”
Section: Resultssupporting
confidence: 84%
“…Our conclusions are comparable with those of other studies conducted for the removal of dyes by adsorption on different materials. Similar findings were published by Ali et al [ 88 ], who explored the adsorption of indigo carmin and Congo Red dyes on calcinated layered double hydroxides, and by Ojediran et al [ 89 ], who inspected the retention of malachite green on acid functionalized maize cob and pointed out that the adsorption does not obey the Langmuir model. Abramian and El-Rassy focused on the adsorption of Orange II dye on a porous titania aerogel [ 79 ] and revealed that the Freundlich isotherm is suitable for describing the process.…”
Section: Resultssupporting
confidence: 84%
“…Studies have shown that the determination of the best isotherm model does not depend only on the R 2 value, and to determine the best isotherm model, coupled with a higher R 2 value, there must be closeness between the data of q e cal and q e exp . 36 In the fitted models, the q e values are 43.25 and 60 for Freundlich and Langmuir isotherms, respectively. These results indicate the best fitting of the Freundlich isotherm, which not only has both linear and nonlinear model values close to 1 but also the q e value is close to the calculated value.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, the nonlinear fitting models have R 2 values of 0.99 and 0.98 for Langmuir and Freundlich isotherms, respectively. Studies have shown that the determination of the best isotherm model does not depend only on the R 2 value, and to determine the best isotherm model, coupled with a higher R 2 value, there must be closeness between the data of q e cal and q e exp . In the fitted models, the q e values are 43.25 and 60 for Freundlich and Langmuir isotherms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The worst fit shows the Halsey isotherm, for which the value of R 2 is <0.1 and the value of χ 2 /DoF is 520 (phosphates ions) and 4320 (chromates ions). The Halsey model is used for multilayer adsorption on the heterogeneous surface [ 76 ], which does not occur with the adsorption performed.…”
Section: Resultsmentioning
confidence: 99%